Synergistic effect of chickpea plants and Mesorhizobium as a natural system for chromium phytoremediation - Velez, Pilar Andrea (2016)
The presence of chromium in soils not only affects the physiological processes of plants but also the microbial rhizosphere composition and metabolic activities of microorganisms. Hence, the inoculation of plants with Cr(VI)-tolerant rhizospheric microorganisms as an alternative to reduce Cr phytotoxicity was studied. In this work, chickpea germination was reduced by Cr(VI) concentrations of 150 and 250 mg/L (6 and 33%, respectively); however lower Cr(VI) concentrations negatively affected the biomass. On the other hand, its symbiont, Mesorhizobium ciceri, was able to grow and remove different Cr(VI) concentrations (5–20 mg/L). The inoculation of chickpea plants with this strain exposed to Cr(VI) showed a significantly enhanced plant growth. In addition, inoculated plants accumulated higher Cr concentration in roots than those noninoculated. It is important to note that Cr was not translocated to shoots independently of inoculation. These results suggest that Mesorhizobium’s capability to remove Cr(VI) could be exploited for bioremediation. Moreover, chickpea plants would represent a natural system for phytoremediation or phytostabilization of Cr in situ that could be improved with M. ciceri inoculation. This strategy would be considered as a phytoremediation tool with great economic and ecological relevance.